Note-Taking Strategy and Students English Achievement at Selective Private Senior High School - Ganap, Dhea; Kondo, Petrus (Civiliza Publishing, Indonesia., 2025)
Note-taking is an essential skill that plays a significant role in academic success. Effective note-taking techniques have been shown to be very helpful while learning a language, such as English. This study sought to determine the relationship between note-taking strategy and student English proficiency at a private senior high school. The questionnaires used in this quantitative investigation were modified versions of those used in the two prior studies by Haghverdi, Biria, and Karimi (2010) and Al-Ashkar (2014). Descriptive and correlation analyses were utilized on the gathered data. The researchers recruited 75 respondents using non-probability sampling techniques in a selected private senior high school’s grade 11 science class to participate in the study. According to the results, students' mean note-taking scores were 3.16, which were evaluated as moderate level, and the mean English achievement score was 72.14, which were regarded as low level. The correlation analysis revealed a significant positive association (p <.000) between note-taking and English achievement. Results are useful to foster effective note-taking strategies, which can contribute to English or academic achievement. A similar study can be done by exploring different variables, respondents, and methodologies.